Modelagem de antenas duplo-refletoras axialmente simétricas através da concatenação de seções cônicas para controle de amplitude e fase na abertura - Adriano Zatti Faria Marques (2020)
An axially symmetrical double-reflector antenna shaping technique is presented. This technique has the differential of simultaneously controlling the phase and amplitude at the aperture of the main reflector, thus controlling the antenna radiation. The generators of the shaped reflectors are composed of concatenated conic sections. At each step of the iterative method, a pair of conics is discovered that form small pieces of the sub-reflector and main reflector of the antenna. The formulation of the iterative shaping method does not present differential and integral equations, thus making the formulation of simple resolution. In the reflector shaping, only trigonometric and conic equations are used. At each step of the iterative method, a system of equations must be solved. However, the equations in this system can be solved sequentially, so that this system of equations can be interpreted as a single function, with only one input variable and returns an error. This error must then be minimized through a numerical solution. The developed technique is applied in two examples of Axially Displaced Cassegrain (ADC) antenna aperture: one with uniform phase and amplitude; and another with non-uniform amplitude and phase for generating a flat topped radiation pattern.